Higher education in the field of arts and culture in the Russian Far East - S. N. Skorinov (Высшее образование в России)
In interview with the rector of Khabarovsk State Institute of Arts and Culture there is briefly reviewed the most important events in the history of the institute on the eve of its 45th jubilee. The prospects of the future development of the university as a Far-Eastern regional and international Asian-Pacific research and education creative centre of preFvocational and vocational personnel training and retraining for arts and culture sphere, which contributes tosocial, economic and cultural development of Russian Far East and its integration into theeconomy of Asian-Pacific region are outlined.